Recent advances in dialysis therapy in Japan - Nakamoto, Hidetomo; Nitta, Kosaku; Tsuchiya, Ken; Okada, Hirokazue; Hasegawa, Hajime (Contributions to nephrology / series editor Claudio Ronco, 2018)
The number of dialysis patients, and their ages, continues to increase globally. This creates major issues such as rising medical costs in an aging population, how to best manage end-of-life care, and how to train the various practitioners involved in dialysis care. After the US and China, Japan occupies 3rd place with regard to the number of dialysis patients and is also widely regarded as a world leader in dialysis. This book contains selected articles - organized into 4 chapters - that discuss recent advances in dialysis therapy in Japan. Chapter 1 presents insights into causes, risk factors, disease associations, and possible implications for management of dialysis patients. Chapter 2 examines recent progress in hemodialysis treatment, and chapter 3 focuses on developments in peritoneal dialysis. The final chapter concentrates on recent advances in apheresis and current trends in practice, among other topics. This book is aimed at nephrologists, physicians, urologists, nurses, clinical engineers, pharmacists, and nutritionists. It is a significant contribution to furthering the progress of dialysis therapy worldwide.